Common femoral vein canal lipoma causing chronic unilateral lower limb swelling. (28th April 2014) - Lowry, Danielle; Kay, Mark Darren; Tiwari, Alok
Abstract : A 64-year-old woman presented to vascular clinic with a 2-year history of right ankle swelling, associated with pain on walking. Initial venous duplex imaging showed no obvious cause. Further imaging showed a lipoma compressing the common femoral vein. We consider the relative merits of the imaging modalities of the groin and the literature available on lipomas causing compression.